A Brief Analysis of Emulation and Innovation in the “Zheng Wengong Stele” - Guo, Jiandong (Pacific International Journal, 2025)
Chinese calligraphy, with its rich historical and artistic heritage, has evolved through various dynastic styles, with the Northern Wei period playing a pivotal role in the development of calligraphic art. This study examines the Zheng Wengong Stele, a representative work of Northern Wei calligraphy, focusing on its artistic and technical significance within the Wei Bei style. The research investigates the historical context of the stele’s creation during the Northern Wei period and analyzes its distinctive brushwork techniques, which combine square and round brushstrokes to achieve a dynamic balance between strength and fluidity. Additionally, the study explores the process of creating a modern model inspired by the stele, demonstrating how traditional techniques can be adapted and innovated for contemporary calligraphy practices. This study highlights its continued influence on the development of Chinese calligraphy and its ongoing role in shaping contemporary artistic expression.